Trends and hot topics in linguistics studies from 2011 to 2021: A bibliometric analysis of highly cited papers - Yan, Sheng; Zhang, Le (Frontiers in Psychology, 2023)
High citations most often characterize quality research that reflects the foci of the discipline. This study aims to spotlight the most recent hot topics and the trends looming from the highly cited papers (HCPs) in Web of Science category of linguistics and language & linguistics with bibliometric analysis. The bibliometric information of the 143 HCPs based on Essential Citation Indicators was retrieved and used to identify and analyze influential contributors at the levels of journals, authors, and countries. The most frequently explored topics were identified by corpus analysis and manual checking. The retrieved topics can be grouped into five general categories: multilingual-related, language teaching, and learning related, psycho/pathological/cognitive linguistics-related, methods and tools-related, and others. Topics such as bi/multilingual(ism), translanguaging, language/writing development, models, emotions, foreign language enjoyment (FLE), cognition, anxiety are among the most frequently explored. Multilingual and positive trends are discerned from the investigated HCPs. The findings inform linguistic researchers of the publication characteristics of the HCPs in the linguistics field and help them pinpoint the research trends and directions to exert their efforts in future studies.